2019
DOI: 10.2169/internalmedicine.2456-18
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary ATTR Amyloidosis with Cardiomyopathy Caused by the Novel Variant Transthyretin Y114S (p.Y134S)

Abstract: We report the clinical features of a patient with hereditary transthyretin (ATTR) amyloidosis associated with a novel mutation (Y114S, p.Y134S). A 65-year-old Japanese man was admitted to our hospital after a 3-year history of progressive dyspnea on exertion. Five years previously, he presented dysesthesia in both hands caused by carpal tunnel syndrome. A genetic analysis revealed a base pair substitution of adenine to cytosine in the second codon of exon 4, residue 114, in the TTR gene (c.401A>C). The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Patients with ATTRv amyloidosis had diverse disease manifestations including polyneuropathy, cardiomyopathy, carpal tunnel syndrome, vitreous opacity, and dementia, according to genetic phenotype and environmental factors. This study found several patients with new mutations in the TTR gene 18,27,28…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Patients with ATTRv amyloidosis had diverse disease manifestations including polyneuropathy, cardiomyopathy, carpal tunnel syndrome, vitreous opacity, and dementia, according to genetic phenotype and environmental factors. This study found several patients with new mutations in the TTR gene 18,27,28…”
Section: Discussionmentioning
confidence: 65%
“…This study found several patients with new mutations in the TTR gene. 18,27,28 Therefore, in this study we reported the different types of amyloidosis and the manifestations of the disease at diagnosis for patients who were referred to our center. These data may contribute to early diagnosis and early intervention to improve the treatment and care of patients with amyloidosis.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Наследственный ATTR-амилоидоз бывает результатом мутации в гене (расположенном на 18q хромосоме и состоящем из 4 экзонов), кодирующем транстиретин, что приводит к замене аминокислот в его молекуле [10]. На сегодняшний день зарегистрировано более 140 различных мутаций в гене транстиретина, большинство из мутаций амилоидогенны, лишь около 10 считаются неамилоидогенными [10,11]. Большинство пациентов являются гетерозиготами, поэтому в организме имеют не только мутантный, а еще нормальный немутантный транстиретин.…”
Section: Introductionunclassified